Technology-Supported Physical Activity and Its Potential as a Tool to Promote Young Women's Physical Activity and Physical Literacy: Systematic Review - Kimberley Watson-Mackie; Lauren Arundell; Natalie Lander; Fiona H McKay; Alethea Jerebine; Fotini Venetsanou; Lisa M Barnett (JMIR Publications, 2024)
BackgroundDespite the known benefits of physical activity (PA), rates of engagement in PA remain low globally. Low engagement in PA among young women can impact their health. Technology-supported PA may increase PA and physical literacy (PL; skills that can support PA) among young women. ObjectiveThis systematic review aims to investigate the (1) associations between technology-supported PA and PA levels, (2) associations between technology-supported PA and PL levels, and (3) types of technology-supported PA that are associated with higher levels of PA engagement among young women aged 13 to 24 years. This age range was chosen as it includes two transitional periods characterized by decreases in PA. MethodsWe searched 6 databases: Applied Science and Technology Source, Education Source, Embase, MEDLINE Complete, Global Health, and SPORTDiscus. Eligible studies were original research published in English between January 1, 2010, and April 24, 2024; focused on young women; and involving either technology-supported PA interventions or research exploring the correlation between technology and PA and PL. The findings of the review were presented descriptively. Study quality was assessed using the JBI Critical Appraisal tools. There were no deviations from the registered protocol. ResultsIn total, 23 (0.1%) studies (10,233 participants) from 23,609 records were included: randomized controlled trials (n=9, 39%), nonrandomized or retrospective observational studies (n=9, 39%), and cross-sectional studies (n=5, 22%). Of the 23 studies, 12 (52%) focused on young adults (aged ≥19 y), 9 (39%) involved adolescents (aged <19 y), and 2 (9%) focused on both groups. Nine studies (39%) were theory based. Common types of technology-supported PA were interactive websites or social media platforms (10/23, 43%), wearable fitness trackers (4/23, 17%), and mobile apps (4/23, 17%). PA or PL were predominantly self-reported (18/23, 78%). A total of 53 PA outcomes were measured: 36% (19/53) reported a positive impact on PA from mobile apps (9/15; 60% of analyses), interactive websites or social media platforms (8/27; 30% of analyses) and wearable fitness trackers (2/11; 18% of analyses). The impact on PL was weak (2/7; 29% of analyses). Eight studies (35%) were rated high, 7 (30%) medium, and 8 (35%) low in quality. ConclusionsThere was limited evidence that technology-supported PA improved young women's PA or PL. The evidence was limited by poor study quality and a lack of theoretical frameworks. In addition, little information was provided on the designs of the technology used. Future interventions seeking to improve young women's PA and PL should focus on the development of mobile apps underpinned by behavior change theory and addressing whole domains of PL rather than specific elements. Given that technology continues to rapidly advance, further studies are needed to demonstrate the impact of technology-supported PA in improving PA and PL among young women.